An integrated multimodal approach to drug repurposing in endometriosis, using ROR1 as a target - Gunther, Kate; Liu, Dongli; Stannard, Gill; Holmes, Melissa; Loo, Christine; Guo, Belinda; Bowden, Nikola; Abbott, Jason; Ford, Caroline E. (Frontiers in Pharmacology, 2025)
BackgroundEndometriosis is a chronic, heterogeneous disease with limited non-hormonal treatment options. Drug repurposing provides an accelerated route to identify safe, tolerable, and potentially effective therapies for endometriosis. Receptor tyrosine kinase-like orphan receptor 1 (ROR1) was investigated as a potential target based on its restricted expression in adult tissues and emerging role in the pathogenesis of multiple diseases.MethodsROR1 expression was assessed in transcriptomic datasets including 408 endometriosis samples and 53 controls and validated at the protein level in an independent cohort of tissue microarrays comprising 179 tissues. Candidate compounds predicted to bind ROR1 were prioritized using the BLAZE platform, filtered for pharmacological safety and patient acceptability, and screened in the 12Z endometriotic epithelial cell line. The compound that showed the greatest reduction in proliferation and viability, rimegepant, was further tested in three patient-derived organoid models representing deep infiltrating endometriosis to evaluate viability, growth, and morphological responses.ResultsROR1 was transcriptionally upregulated in endometriosis and overexpressed at the protein level across lesions. Of three shortlisted compounds, cabergoline and pirenzepine did not alter proliferation, while rimegepant significantly reduced viability in 12Z cells. In patient-derived organoids, responses were patient-specific: two models showed concentration-dependent antiproliferative and cytotoxic effects, while one model was less responsive at the concentrations tested. Morphological features consistent with cell death were observed in sensitive lines.ConclusionThis study provides the first evidence in human-derived endometriosis models supporting rimegepant, a clinically approved calcitonin gene-related peptide antagonist with a favorable safety profile, as a potential therapy. The integrated pipeline combining molecular validation, computational prioritization, and patient-derived functional testing illustrates a translational approach to accelerate drug discovery in endometriosis.